EFEKTIVITAS PUPUK ORGANIK TERHADAP PRODUKTIVITAS TANAMAN KAKAO DI SULAWESI TENGGARA - nFN Agussalim (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACTThe Effectiveness of Organic Fertilizers on Cocoa Productivity in Southeast Sulawesi. The study purposed to determine the effectiveness of the use of organic fertilizers on cocoa plants. The research was conducted in Andomesinggo Village, Besulutu Sub District, Konawe District, Southeast Sulawesi Province. The study used a randomized block design with 5 treatments and 6 replications. The treatments for each trees consisted of: 1) 300 ginorganic fertilizers (phonska) + 150 g urea; 2) 250 g organic fertilizer + 225 g phonska + 112.5 urea; 3) 500 g organic fertilizer + 150 g phonska + 75 g urea; 4) 750 g organic fertilizer + 75 g phonska + 37.5 g urea; and 5) 1.000 g organic fertilizers. Observations were made on (1) the generative growth, namely; interest bearing, valve, the amount of fruit, and (2) the results, which include the dry weight of seed and plant productivity. Results of the study showed that (a) organic fertilizers can be combined with inorganic fertilizers, (b) provision of 250 g organic fertilizer + 225 g phonska + 112.5 g of urea and 500 g organic fertilizer Phonska + 150 g + 75 g of urea or 25% -50% organic fertilizer was the best combination and (c) the use of organic fertilizer on cocoa crop to be economically viable with the B/C > 0 or R/C > 1. The use of organic fertilizer gave positive effects to increase cocoa productivity through grain weight cocoa, however the productivity effectiveness level depends on the balance with a dose of urea and Phonska.Keywords: effectiveness, organic fertilizer, cocoa, environmentABSTRAKPenelitian bertujuan untuk mengetahui efektivitas pupuk organik pada tanaman kakao. Penelitian dilaksanakan di Desa Andomesinggo, Kecamatan Besulutu, Kabupaten Konawe, Provinsi Sulawesi Tenggara. Penelitian menggunakan rancangan acak kelompok dengan 5 perlakuan dan 6 ulangan. Perlakuannya sebagai berikut;1) 300 g phonska pupuk anorganik + 150 g urea/pohon; 2) pupuk organik 250 g + 225 g phonska + 112,5 urea/pohon; 3) 500 g pupuk organik +150 g phonska+75 g urea/pohon; 4) 750 g pupuk organik + 75 g phonska + 37,5 g urea/pohon; dan 5) 1.000 g pupuk organik /pohon. Pengamatan dilakukan terhadap (1) pertumbuhan generatif yaitu:bantalan bunga, pentil, jumlah buah, serta (2) hasil, yang meliputi bobot kering biji dan produktivitas tanaman. Hasil penelitian menunjukkan hasil bahwa: (a) pupuk organik dapat dikombinasikan dengan pupuk anorganik, (b) pemberian 250 g pupuk organik + 225 g phonska + 112,5 g urea dan 500 g pupuk organik + 150 g phonska + 75 g urea atau 25%-50% pupuk organik merupakan kombinasi terbaik dan (c) penggunaan pupuk organik pada tanaman kakao secara ekonomi layak dengan B/C >0 atau R/C >1. Penggunaan pupuk organik berperan positif dapat meningkatkan produktivitas kakao melalui pengaruhnya pada pembentukan biji, namun tingkat efektivitasnya terhadap produktivitas tergantung pada keseimbangan dengan dosis pupuk phonska dan urea.Kata kunci: efektivitas, pupuk organik, kakao, lingkungan